Multifaceted determinants for achieving glycemic control the international diabetes management practice study (IDMPS) - Chan, Juliana C. N. (2009)
OBJECTIVE - The International Diabetes Mellitus Practice Study is a 5-year survey documenting changes in diabetes treatment practice in developing regions. RESEARCH DESIGN AND METHODS - Logistic regression analysis was used to identify factors for achieving A1C <7% in 11,799 patients (1,898 type 1 diabetic and 9,901 type 2 diabetic) recruited by 937 physicians from 17 countries in Eastern Europe (n = 3,519), Asia (n = 5,888), Latin America (n = 2,116), and Africa (n = 276). RESULTS - Twenty-two percent of type 1 diabetic and 36% of type 2 diabetic patients never had A1C measurements. In those with values for A1C, blood pressure, and LDL cholesterol, 7.5% of type 1 diabetic (n = 696) and 3.6% of type 2 diabetic (n = 3,896) patients attained all three recommended targets (blood pressure < 130/80 mmHg, LDL cholesterol <100 mg/dl, and A1C <7%). Self-monitoring of blood glucose was the only predictor for achieving the A1C goal in type 1 diabetes (odds ratios: Asia 2.24, Latin America 3.55, and Eastern Europe 2.42). In type 2 diabetes, short disease duration (Asia 0.97, Latin America 0.97, and Eastern Europe 0.82) and treatment with few oral glucose-lowering drugs (Asia 0.64, Latin America 0.76, and Eastern Europe 0.62) were predictors. Other region-specific factors included lack of microvascular complications and old age in Latin America and Asia; health insurance coverage and specialist care in Latin America; lack of obesity and self-adjustment of insulin dosages in Asia; and training by a diabetes educator, self-monitoring of blood glucose in patients who self-adjusted insulin, and lack of macrovascular complications in Eastern Europe. CONCLUSIONS - In developing countries, factors pertinent to patients, doctors, and health care systems all impact on glycemic control.